COVID-19 disruptions and pivoting in SMEs in the hidden middle of Kenya’s potato and fish value chains - Naziri, D.; Belton, Ben; Alobo Loison, Sarah; Reardon, Thomas; Shikuku, Kelvin Mashisia; Kaguongo, W.; Maina, K.; Ogello, E.; Obiero, K. (Brill, 2023)
Small and medium enterprises (SMEs) in Kenya were severely affected by the COVID-19 pandemic and restrictions put in place to contain it. This study assesses the impact of these restrictions on the midstream of the potato and fish value chains, with a focus on traders and processors, and investigates the short- and longer-term responses and ‘pivoting’ strategies deployed by these firms. Longitudinal data were collected from 937 respondents with three recall periods: (1) the pre-pandemic situation (2019); (2) the period of strictest restrictions, necessitating immediate adaptations by firms (2020); and (3) a period of anticipated recovery with longer-term business adaptation strategies (2021). Firms in both value chains reported a dramatic drop in turnover in 2020. Potato SMEs partially recovered in 2021, but fish SMEs reported further declines in turnover. In the face of restrictions, SMEs shifted toward more localized procurement and sales, shorter supply chains (often by-passing intermediaries and increasing use of contracts), use of smaller vehicles, and toward the adoption of information and communication technology (ICT) to search for and engage with business partners. Smaller firms and the biggest of businesses were more resilient and less subject to large fluctuations in business turnover, suggesting an inverted U-shape relationship between firm size and impact. Firms located close to production areas and selling primarily within their own county were also less affected. We provide recommendations for increasing business resilience to shocks based on these findings.